Plasma Renin Concentration is Associated With Hemodynamic Deficiency and Adverse Renal Outcome in Septic Shock. Issue 4 (October 2019) - Nguyen, Maxime; Denimal, Damien; Dargent, Auguste; Guinot, Pierre-Grégoire; Duvillard, Laurence; Quenot, Jean-Pierre; Bouhemad, Bélaïd
ABSTRACT: Background: In septic shock, both systemic vasodilatation and glomerular arteriole dilatation are responsible for the drop in glomerular filtration observed in early acute kidney injury. Angiotensin II has been shown to act on both mechanisms. Our objective was to evaluate the impact of renin angiotensin system activation, on hemodynamic deficiency and renal outcome in patient with septic shock and to assess whether urinary sodium could be a reliable test for high plasma renin concentration screening. Methods: This was a prospective and observational study. Inclusion criteria were early septic shock (first episode), dose of norepinephrine ≥ 0.25 μg/kg/min, before the start of substitutive corticosteroids. Plasma renin concentration, plasma aldosterone concentration, and urinary sodium were measured at inclusion. Renal outcome, organ deficiency, and 28-day survival were followed. Results: Plasma renin concentration was associated with worse hemodynamic deficiency and adverse renal outcome. Natriuresis was associated with shock severity but was not associated with renal outcome. Low natriuresis (< 20 mM) was associated with higher renin concentration. Those two variables were only weakly correlated. Conclusion: Plasma renin concentration is associated with adverse renal outcome, probably through shock severity and insufficient glomerular efferent arterioles vasoconstriction. An association was observed between low natriuresis and high plasma renin concentration.